Exploring behaviours of concern including aggression, self-harm, sexual harm and absconding within an Australian inpatient mental health service. (August 2020) - Kang, Matthew; Bushell, Hannah; Lee, Stuart; Berry, Caitlin; Hollander, Yitzchak; Rauchberger, Ilan; Whitecross, Fiona
Objective: Patients admitted to mental health services may exhibit behaviours of concern (BOCs) such as aggression, self-harm, absconding and sexual harm. BOCs can lead to restrictive interventions, which have adverse effects on patients, carers and staff. This paper aims to explore the nature and outcome of BOCs within an adult inpatient mental health setting. Methods: A retrospective audit was conducted at a metropolitan inpatient service between 1 August 2016 and 31 July 2017. The frequency, nature and outcomes of BOC episodes were described and thematic analysis was used to summarise BOC antecedents. Results: A BOC was documented for 179 (18.2%) patients who also showed high rates of drug abuse, homelessness and longer admission. Most self-harm and sexual harm events occurred outside of normal business hours. Medications and verbal de-escalation were commonly used interventions. Episodes of deliberate self-harm were likely to result in patient and staff injury or mechanical restraint, whereas aggression was associated with seclusion. Mental state, care engagement, physiological stress and situational stressor were identified as BOC antecedents. Conclusion: Multiple forms of BOCs were experienced with mental state, physical and interpersonal contributors identified. Improving multidisciplinary input into early assessment and treatment of BOC causes is needed to improve safety.